2006
DOI: 10.1007/s10591-006-9001-3
|View full text |Cite
|
Sign up to set email alerts
|

“Almost There”...Why Clients Fail to Engage in Family Therapy: An Exploratory Study

Abstract: A great deal of clinical research has sought to describe and suggest remedies for the client dropout phenomenon. However, few studies have addressed the equally pervasive, yet often ignored, non-engagement problem. An exploratory study was conducted to understand why many clients fail to engage in family therapy services after they have completed the initial intake. The results of the study suggest that therapist gender and experience level, clinic policies regarding videotaping sessions, family concerns, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Couple and family treatment also requires engagement of more clients with different priorities or goals. Unfortunately, unwillingness of family members to attend therapy sessions contributes to non-engagement in therapy (Wang et al, 2006). …”
Section: Importance Of Technology For Family and Couple Interventionsmentioning
confidence: 99%
“…Couple and family treatment also requires engagement of more clients with different priorities or goals. Unfortunately, unwillingness of family members to attend therapy sessions contributes to non-engagement in therapy (Wang et al, 2006). …”
Section: Importance Of Technology For Family and Couple Interventionsmentioning
confidence: 99%
“…One of the key components of success in family therapy is attributed to the therapist's capacity to engage and retain the family in treatment (Stanton & Shadish, 1997;Wang et al, 2006). Research on clients' perceptions of family therapy suggests that therapists' rapport, warmth, optimism, humor, and commitment are crucial aspects of effective treatment (Beck, Friedlander, & Escudero, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The presented analysis shows the connection between the drop-out phenomenon with elements of the therapeutic process, such as alliance or the therapeutic bond and with the conflict present in the couple. The categories and processes which were distinguished can be referred to research studies associating drop-out with a failure to conceptualize the problem [33,34] and a failure to define mutual expectations about the method of solving this problem [13,35,36] as well as to studies which emphasize the importance of establishing a therapeutic alliance with at least two persons [28]. It should also be underlined that split alliances mostly appear at the beginning of therapeutic processes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of cooperation in the therapy of one person is a significant factor decreasing the involvement in the therapy [26]. As a larger number of patients/clients are involved in family therapy or couple therapy than during individual therapy, it can be concluded that the lack of involvement in the therapy on the part of one person also contributes to a larger number of drop-outs in family and couple therapy [27][28]. However, the involvement and motivation for therapy should not be treated as the same factor for the therapy, as research shows [24] it is important to understand internal alliances and splitting which occur between the individual persons in a family and a couple.…”
Section: Split Working Alliancementioning
confidence: 99%